Sleep, internalizing symptoms, and health-related quality of life in children with neurodevelopmental disorders: a cross-sectional analysis of cohort data from three research programs in Canada - McPhee, Patrick G.; Georgiades, Stelios; Andrade, Andrea; Corkum, Penny V.; Vaccarino, Anthony L.; Cheema, Heena; Chepesiuk, Rachel; Iaboni, Alana; Gorter, Jan Willem; , The OBI Cross-integrated Discovery Program Sleep Team (Frontiers in Sleep, 2023)
Children with neurodevelopmental disorders from a cross-sectional study experienced a greater rate of sleep disturbances (n=659; 78.6%) compared to typically developing children (n=50; 41.6%).• Sleep disturbances and internalizing symptoms were significantly negatively associated with health-related quality of life in children with neurodevelopmental disorders.• No significant differences between neurodevelopmental disorders were found for bedtime resistance, sleep anxiety, night wakings, parasomnias, and sleep disordered breathing.• Collaboration between clinicians, researchers, and families is needed to promote transdiagnostic interventions across neurodevelopmental disabilities to ensure that adequate resources and supports are available to children and their families to optimize sleep behaviours, everyday functioning, and quality of life.